Lower Extremity Cutaneous Lesions as the Initial Presentation of Metastatic Adenocarcinoma of the Colon - Dhyan Rajan; Mitanshu Shah; Pooja Raghavan; Shanza Mujeeb; Sadat Rashid; Aieska Desouza; Paul Mustacchia (Case Reports in Medicine)
Cutaneous metastases from colorectal cancers are rare and are usually present on the abdominal wall or previous surgical incision sites. Remote cutaneous lesions have been reported, however, often occur in the setting of widespread metastatic disease including other visceral secondaries. We present a case of lower extremity cutaneous metastases as the first sign of metastatic disease in a patient with adenocarcinoma of the colon. This case illustrates that new skin lesions may be the initial presentation of metastatic disease in a patient with a history of cancer.